Central nervous system tumefactive demyelinating lesions: Risk factors of relapse and follow-up observations - Li, Xinnan; Miao, Xiuling; Wang, Yaming; Sun, Junzhao; Gao, Haifeng; Han, Jing; Li, Yuxin; Wang, Qingjun; Sun, Chenjing; Liu, Jianguo (Frontiers in Immunology, 2022)
Objective To track the clinical outcomes in patients who initially presented with tumefactive demyelinating lesions (TDLs), we summarized the clinical characteristics of various etiologies, and identified possible relapse risk factors for TDLs. Methods Between 2001 and 2021, 116 patients initially presented with TDLs in our hospital were retrospectively evaluated. Patients were followed for relapse and clinical outcomes, and grouped according to various etiologies. Demographic information, clinical data, imaging data, and laboratory results of patients were obtained and analyzed. The risk factors of relapse were analyzed by the Log-Rank test and the Cox proportional hazard model in multivariate analysis. Result During a median follow-up period of 72 months, 33 patients were diagnosed with multiple sclerosis (MS), 6 patients with Balo, 6 patients with neuromyelitis optica spectrum disorders (NMOSD), 10 patients with myelin oligodendrocyte glycoprotein antibody-associated demyelination (MOGAD), 1 patient with acute disseminated encephalomyelitis (ADEM), and the remaining 60 patients still have no clear etiology. These individuals with an unknown etiology were categorized independently and placed to the other etiology group. In the other etiology group, 13 patients had recurrent demyelinating phases, while 47 patients did not suffer any more clinical events. Approximately 46.6% of TDLs had relapses which were associated with multiple functional system involvement, first-phase Expanded Disability Status Scale score, lesions morphology, number of lesions, and lesions location (P<0.05). And diffuse infiltrative lesions (P=0.003, HR=6.045, 95%CI:1.860-19.652), multiple lesions (P=0.001, HR=3.262, 95%CI:1.654-6.435) and infratentorial involvement (P=0.006, HR=2.289, 95%CI:1.064-3.853) may be independent risk factors for recurrence. Relapse free survival was assessed to be 36 months. Conclusions In clinical practice, around 46.6% of TDLs relapsed, with the MS group showing the highest recurrence rate, and lesions location, diffuse infiltrative lesions, and multiple lesions might be independent risk factors for relapse. Nevertheless, despite extensive diagnostic work and long-term follow-up, the etiology of TDLs in some patients was still unclear. And these patients tend to have monophase course and a low rate of relapse.